Sulfinyl isobutyramide as an auxiliary for palladium(ii)-catalyzed C–H arylation and iodination of benzylamine derivatives. Issue 23 (2nd June 2017) - Wang, Rui; Ding, Yongzheng; Li, Gang
Abstract : An original readily available and versatile bidentate 2-methylsulfinyl isobutyramide directing group has been developed for benzylamine derivatives. Abstract : A novel readily available bidentate 2-methylsulfinyl isobutyramide directing group has been developed for benzylamine derivatives. It promoted ortho -C–H arylation and iodination of various substrates in good to excellent yields. The auxiliary is promising to be used in organic synthesis due to its versatility and convenient preparation from inexpensive materials.